PENGARUH PENGGUNAAN EKSTRAK DAUN JAMBU BIJI (Psidium guajava L.) TERHADAP MORTALITAS EMBRIO, DAYA TETAS, DAN SALEABLE ITIK HIBRIDA - Andre Pangestu; Khaira Nova; Dian Septinova; RR Riyanti (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2021)
This study aimed to determine the effect of immersion of hybrid duck eggs using guava leaf extract at different concentrations on embryo mortality, hatchability, and saleable duck. The research was conducted in March - April 2020. Guava leaf extract was made at the Animal Production and Reproduction Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The dyeing and hatching treatments were carried out in Hajimena Village, Natar District, South Lampung. This study used a completely randomized design (CRD) with four treatments, namely without immersing guava leaf extract (P0), immersing with guava leaf extract concentrations of 10% (P1), 20% (P2), and 30% (P3). The results showed that the percentage of embryo mortality without dyeing and immersing guava leaf extract concentrations of 10, 20, and 30% were 40.00%, 24.00%, 16.00%, and 28.00%, respectively. Hatchability of hybrid duck eggs in the treatment without immersion and immersion in guava leaf extract concentrations of 10, 20, and 30% were 60.00, 76.00, 84.00, and 72%, respectively. Saleable duck duck eggs without immersion 93.34% and immersion in guava leaf extract with concentrations of 10, 20, and 30% respectively were 100.00%. It was concluded that immersion of hybrid duck eggs using guava leaf extract at concentrations of 10.00, 20.00, and 30.00% decreased the percentage of mortality, increased hatchability, and increased the salable duck. Keywords: Hybrid duck, Guava leaves extract, Embryonic mortality, Hatchability, Saleable duck